Implementation of Digital Invitation Applications in The Era Society 5.0 As a Business Opportunity Micro Small to Medium (MSMEs) - Priyatna, Bayu; Tia Hananto, Agus; Huda, Baenil (Information System; Universitas Buana Perjuangan Karawang, 2024)
Indonesian people have a great opportunity to become MSMEs. One of the MSME players is utilizing digital technology as an innovative product. One of the phenomena slowly transferring to a society or society that was using paper has now changed into digital invitations. Invitations are digital or electronic and can be accessed via a computer, tablet, or smartphone. Digital invitations canbe in images, videos, or text messages created using graphic design or special digital invitation applications. Typically, Digital Invitations include information about the event, such as date, time, place, and theme. Digital Invitations can also be decorated with images, icons, or illustrations related to the event. The advantages of using Digital invitations include a practical and easy-to-disseminate, cost-effective, and more friendly environment that can be accessed anytime. In contrast to conventional invitations, they are susceptible to damage, require additional costs, limit design options, take time to print and ship, and generate waste. Method The research used was descriptive with a qualitative approach through interviews exploring several printed invitation and wedding organizer service providers in Karawang. Research results on digital invitation applications can help MSMEs expand market reach, increase time and cost efficiency, and deliver a more interactive and personalized customer experience.